How has organization benefited women in the Barbados flyingfish fishery? A look from within. (2nd January 2020) - Pena, Maria; McConney, Patrick; Simmons, Bertha; Selliah, Neetha
Abstract: Collective action and the diversity of forms it may take in fisherfolk organizing is complex. Efforts to implement the 2014 Voluntary Guidelines for Securing Sustainable Small-Scale Fisheries in the Context of Food Security and Poverty Eradication (SSF Guidelines) have resulted in increasing global to local attention on fisherfolk organizations, their strengthening and governance. These include women's roles and participation in them, both as members and as leaders. There is limited literature on women in fisherfolk organizations in Barbados. Women in the flyingfish postharvest sector are conspicuous, but how some work through their fisherfolk organization is undocumented. The Central Fish Processors Association (CFPA) formed to address challenges small fish processors were experiencing in their livelihoods. Through group interviews and document analysis, benefits to the women from participation in this all-woman organization, and the challenges they face, were explored by examining the links between collective action, organization and gender. We document the collective action of these women in preparing to make practical interventions for improvements to their working and domestic lives. It is the first research focused on organized women in the Barbados flyingfish fishery, deviating from the typical focus on men in its harvest sector.